PENGARUH MODEL CORE BERBANTUAN MEDIA MOBA RAKSA TERHADAP KEMAMPUAN PEMAHAMAN KONSEP DAN TANGGUNG JAWAB SISWA - Salsabilla Maulida Setiawan; Kartika Yuni Purwanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effect of the CORE (Connecting, Organizing, Reflecting, Extending) learning model assisted by MoBa Raksa media on students conceptual understanding and responsibility attitudes in elementary school. This research employed a quantitative approach using a quasi-experimental method with a nonequivalent control group design. The research subjects were fourth-grade students of SD Negeri Susukan 01, consisting of an experimental class and a control class. Data were collected using tests, observations, and questionnaires. The test technique was used to measure students’ conceptual understanding before and after the implementation of the learning model. Observation was conducted to examine the implementation of the CORE learning model and students’ responsibility attitudes during the learning process, while questionnaires were used to measure students’ responsibility attitudes quantitatively. The collected data were analyzed using statistical tests, including normality tests, homogeneity tests, independent sample t-tests, and simple linear regression analysis. The results of the study indicate that there is a significant difference in students’ conceptual understanding between the class taught using the CORE learning model assisted by MoBa Raksa media and the class taught using conventional learning. Furthermore, the findings show a positive and significant effect of the CORE learning model assisted by MoBa Raksa media on students’ responsibility attitudes. These results suggest that integrating the CORE learning model with educational game-based media can create an active, meaningful, and student-centered learning environment. Therefore, the CORE learning model assisted by MoBa Raksa media is effective as an alternative instructional approach to improve students conceptual understanding and responsibility attitudes in elementary schools.